Impact of First Order Slip Condition on Peristaltic Transport of a Pseudoplastic Fluid Under MHD Effect Bounded by Permeable Walls with Suction and Injection (Contemporary Mathematics, 2025)
This research investigates the impact of first-order slip conditions on the peristaltic flow of a pseudoplastic fluid in the presence of a magnetic field, taking into the effects of suction and injection. Pseudoplastic fluids, which are shear-thinning, undergo a reduction in viscosity as shear rate increases, as opposed to Newtonian fluids, which maintain a constant viscosity regardless of applied shear stress. This characteristic is commonly found in fluids such as blood, polymer solutions, and certain industrial slurries, making them well-suited for applications where efficient flow under stress is critical. The analytical solution for frictional force and pressure rise was derived using perturbation techniques, assuming a long wavelength and low Reynolds number. Matrix Laboratory (MATLAB) simulations provided visual insights into how key parameters such as the magnetic field strength M, the slip parameter α, and the suction and injection parameter k influence velocity profiles, pressure distribution, and friction forces. The findings indicate that a magnetic field M increases the fluid’s pumping efficiency, while a higher slip parameter α enhances the perturbation parameter Γ. Additionally, increasing the suction and injection parameters improves the overall pressure gradient, leading to more effective fluid transport across the system.
Keywords: shear-thinning behavior, suction and injection, peristaltic transport, magnetohydrodynamic (MHD)